Measurement of Information Technology Management Capability Using COBIT 5.0 in The Facility Management Department of PT Permata Graha Nusantara - Chui, Alexander Alvin; Wella, Wella (Universitas Multimedia Nusantara, 2024)
IT governance is the responsibility of the board of directors and executive management of a company that ensures the company information technology supports and expands the company strategy and objectives. But IT governance that does not support departments can have a negative or detrimental impact on the department. For this reason, it is necessary to take measurements to see the level of IT governance that is currently being implemented. The Facility Management Department is a department of PT Permata Graha Nusantara which is engaged in building management services that wants to see whether the ongoing IT system provides support to operational activities and provides better services to customers. To measure the capability of IT governance, the COBIT 5.0 framework is used as a reference in this study. Domain selection is done according to COBIT 5.0 standard and on the selection of the department 5 domains are tested, namely APO05 Manage Portfolios, APO10 Manage Suppliers, APO11 Manage Quality, BAI04 Manage Availability and Capacity, and DSS03 Manage Problems. Each domain chosen to have different aims and objectives and measured using standards set by the COBIT 5.0 framework. The measurement results are Capability Level which has levels from level 0 to 5. The target expected by the Facility Management department is level 4, but the results obtained are not in line with expectations and get level 3 in each domain tested, so this department must make improvements based on recommendations made based on the COBIT 5.0 framework.